2011
DOI: 10.5194/angeo-29-573-2011
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the inter-hemispheric field-aligned current system in the equatorial ionosphere as observed by CHAMP

Abstract: Abstract. From geomagnetic field observations of CHAMP during [2001][2002][2003][2004][2005][2006][2007][2008][2009] we extracted characteristic signatures of inter-hemispheric field-aligned currents (IHFACs) in the equatorial ionosphere. The results are in general agreement with previous observations. Nighttime IHFACs are negligibly small. Solstitial IHFACs flow from the summer to winter (from winter to summer) hemisphere at dawn (around noon). Duskside IHFACs flow southbound irrespective of season. We have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
110
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(137 citation statements)
references
References 35 publications
21
110
6
Order By: Relevance
“…[60] It is noticeable in Figure 10 that the positive ΔD, southward flow, in December is centered around 15 LT, rather than noon, and this closely agrees with the results of Park et al [2011].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…[60] It is noticeable in Figure 10 that the positive ΔD, southward flow, in December is centered around 15 LT, rather than noon, and this closely agrees with the results of Park et al [2011].…”
Section: Discussionsupporting
confidence: 79%
“…Noon FACs are deduced from the tilt of the current system. Afternoon/dusk results are harder to interpret: it seems that our results agree more closely with the Fukushima model than with the satellite results of Park et al [2011], though the satellite currents are earlier in local time.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Yamashita and Iyemori (2002) analyzed magnetic data from the Ørsted satellite to study the seasonal climatology of the inter-hemispheric field-aligned currents. Park et al (2011) showed a comprehensive seasonal, local-time and longitudinal climatology of the inter-hemispheric field-aligned currents based on 9 years of magnetic field measurements by the CHAMP (CHAllenging Minisatellite Payload) satellite. Lühr et al (2015) used measurements from the Swarm satellite constellation.…”
Section: Inter-hemispheric Field-aligned Currentsmentioning
confidence: 99%